Dendron to Central Core S1–S1 and S2–Sn (n>1) Energy Transfers in Artificial Special Pairs Containing Dendrimers with Limited Numbers of Conformations. Issue 13 (1st February 2013) - Harvey, Pierre D.; Brégier, Frédérique; Aly, Shawkat M.; Szmytkowski, Jędrzej; Paige, Matthew F.; Steer, Ronald P.
Abstract Two dendrimers consisting of a cofacial free‐base bisporphyrin held by a biphenylene spacer and functionalized with 4‐benzeneoxomethane (5‐(4‐benzene)tri‐10, 15, 20‐(4‐n‐octylbenzene)zinc(II)porphyrin) using either five or six of the six available meso‐positions, have been synthesized and characterized as models for the antenna effect in Photosystems I and II. The presence of the short linkers, ‐CH2O‐, and long C8H17 soluble side chains substantially reduces the number of conformers (foldamers) compared with classic dendrimers built with longer flexible chains. This simplification assists in their spectroscopic and photophysical analysis, notably with respect to fluorescence resonance energy transfer (FRET). Both steady‐state and time‐resolved spectroscopic measurements indicate that the cofacial free bases and the flanking zinc(II)–porphyrin antennas act as energy acceptor and donor, respectively, following excitation in either the Q or Soret bands of the dendrimers. The rate constants for singlet electronic energy transfer (kEET) extracted from the S1 and S2 fluorescence lifetimes of the donor in the presence and absence of the acceptor are ≤ (0.1–0.3)×109 and ∼2×109 s−1 for S1→S1 (range from a bi‐exponential decay model) and about 1.5×1012 s−1 for S2→Sn (n>1). Comparisons of these experimental data with those calculated from Förster theory using orientation factors and donor–acceptor distances extracted from computer modeling suggest that a highly restricted number of the many foldamers facilitate energy transfer. These foldamers have the lowest energy by molecular modeling and consist of one or at most two of the flanking zinc porphyrin antennas folded so they lie near the central artificial special pair core with the remaining antennas located almost parallel to and far from it.